(untitled) (Eurasian Scientific Herald, 2023)
The article discusses the importance, features and options for increasing the throughput of mobile telecommunications networks, the development of the telecommunications sector, the article writes about increasing the throughput on the transit networks of mobile operators (TS) in its functions is similar to long-distance and international fixed networks. And it describes the signaling system of SS No. 7, about its capabilities related to the management of conversational and signaling traffic in changing conditions on the transit network, as well as to increase the efficiency of using network resources.